Incarceration Rates and Incidence of Sexually Transmitted Infections in US Counties, 2011–2016 - Nowotny, Kathryn M. (Am J Public Health, 2020)
Objectives. To examine rates of sexually transmitted infections as a function of jail and prison incarceration rates across US counties for the years 2011 to 2016. Methods. We used data from several national databases. The outcomes were county-level chlamydia and gonorrhea incidence as reported by the Centers for Disease Control and Prevention (2012–2016). The exposures were lagged specifications of county-level jail and prison incarceration rates as reported by the Vera Institute of Justice (2011–2015). We estimated mixed models to account for the 3 sources of response variable variation occurring across repeated measures collected from counties nested within states. Results. In the final model, jail and prison incarceration rates were associated with a rate increase of 10.13 per 100 000 and 8.22 per 100 000, respectively, of chlamydia incidence. The corresponding rate increases for gonorrhea incidence were 2.47 per 100 000 and 4.40 per 100 000. Conclusions. These findings provide some evidence that the documented differences in chlamydia and gonorrhea incidence between counties may be partially attributable to differences in jail and prison incarceration rates.